2017
DOI: 10.1002/adem.201700084
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of AlSi7Mg with Oxide Ceramics

Abstract: The development of new active filters for the melt filtration in aluminum industry requires investigations of the interaction of aluminum and its alloys with novel filter materials. The requested filter effects require information about the wettability and potential chemical reactions between the filter material and the metal. Wetting experiments (sessile drop technique at 950 C under vacuum) of an AlSi7Mg alloy on oxide ceramics (Al 2 O 3 , MgAl 2 O 4 , 3Al 2 O 3 Á 2SiO 2 , TiO 2 ) in two different surface qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Contact angles lower than 90° [ 7 ] indicated a good wetting behavior contradicting the statement of the good slagging resistance due to a poor wetting. Fankhänel et al [ 11 ] proved the occurrence of chemical reactions between several oxide ceramics and an AlSi7Mg alloy during the sessile drop measurements at 950 °C contrary to the measurements performed at 730 °C [ 3 ]. The substrate based on MgAl 2 O 4 showed an impoverishment of Mg after the sessile drop measurements at 950 °C, whereas the same substrate featured no chemical changes after the sessile drop measurements at 730 °C [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contact angles lower than 90° [ 7 ] indicated a good wetting behavior contradicting the statement of the good slagging resistance due to a poor wetting. Fankhänel et al [ 11 ] proved the occurrence of chemical reactions between several oxide ceramics and an AlSi7Mg alloy during the sessile drop measurements at 950 °C contrary to the measurements performed at 730 °C [ 3 ]. The substrate based on MgAl 2 O 4 showed an impoverishment of Mg after the sessile drop measurements at 950 °C, whereas the same substrate featured no chemical changes after the sessile drop measurements at 730 °C [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contact angles lower than 90 • [7] indicated a good wetting behavior contradicting the statement of the good slagging resistance due to a poor wetting. Fankhänel et al [11] proved the occurrence of chemical reactions between several oxide ceramics and an AlSi7Mg alloy during the sessile drop measurements at 950 • C contrary to the measurements performed at 730 The contact angle of pure Al2O3 was above 140° at the beginning of the dwell time at 950 °C and decreased systematically during the dwelling time down to an almost stable contact angle of 100°. The initial decrease of the contact angle indicated that the decomposition of the oxide skin on the aluminum alloy finalized when reaching a stable contact angle.…”
Section: Sessile Drop Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…These values have been compiled in Table 1 mainly for comparison purposes, since a previous study revealed that the wetting behavior of Al–Si melts towards a series of filter substrate materials varied only slightly in the present range of roughness. [ 31 ] The Al 2 O 3 –C and SiC substrates were quite dense, while mullite and spinel provided higher roughness than the rest of the substrates. The roughness of Al 2 O 3 exhibited intermediate roughness values compared with the other filter materials.…”
Section: Methodsmentioning
confidence: 99%
“…Expanding the application of filters beyond the industrially established removal of nonmetallic inclusions [ 31,32 ] to increase the Fe‐removal efficiency, may further contribute to the production of high‐quality, recycled Al–Si alloys. During the past years, new filtering techniques and new active filter materials have been developed to expand the range of application and to improve filter efficiency.…”
Section: Introductionmentioning
confidence: 99%